Tinjauan Yuridis Perundungan di Pendidikan Kedokteran - Sudarmanto, Alif Muhammad; Wisnuwardhana, Aldi Maheswara; Aufa, Ilma Mufidatul; Adiwijaya, Janice Nathania; Ricardo, William; Bhima, Sigid Kirana Lintang; Hartiana, Kristianti (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 13 No 2 (2024)DO - 10.24843/JMHU.2024.v13.i02.p12., 2024)
Bullying is an act against the medical code of ethics, but its presence is still found in medical education. Institutionalized behavior, stressful work environment, and lack of policies on bullying makes bullying prevention difficult, despite knowledge and understanding of the law in 92% of physicians. This study aims to judicially review the regulations related to bullying so that there is a reference for evaluating the existing protection mechanisms. Normative juridical approach was utilized with secondary data as the data source, such as regulations and research journals. This research found that there were several types of bullying, namely verbal, social, physical, cyber, and financial. Verbal bullying was the most common type of bullying, while physical bullying was the rarest type. When bullying was about to be linked to a criminal act or in a civil manner, there were several aspects that must be taken into account before linkage. Currently, the available laws and regulations, such as those in the Criminal Code, Civil Code, and the Electronic Information and Technology Law, were able to bind perpetrators of bullying in general. Specific regulations, such as the Act Number 17 Year 2023 regarding Health, had regulated bullying in the medical environment, including education. Regulations that more thoroughly accommodate the regulation bullying and up-to-date research regarding the strength of legal mechanisms related to bullying would still be urgently needed. Perundungan merupakan tindakan yang tidak sesuai dengan kode etik kedokteran, tetapi kehadirannya masih ditemukan di pendidikan kedokteran. Perilaku yang tertanam dalam institusi, lingkungan kerja yang menekan, dan kurangnya kebijakan terkait perundungan membuat pencegahan perundungan sulit, terlepas dari pengetahuan dan pemahaman hukum sebesar 92% di kalangan dokter. Penelitian ini bertujuan untuk meninjau secara yuridis peraturan terkait perundungan agar terdapat acuan untuk mengevaluasi mekanisme perlindungan yang telah ada saat ini. Pendekatan yuridis normatif digunakan dengan jenis data berupa data sekunder, seperti peraturan dan jurnal penelitian. Terdapat beberapa jenis perundungan, yakni verbal, sosial, fisik, siber, dan finansial. Perundungan verbal merupakan perundungan yang paling sering ditemukan, sedangkan fisik merupakan jenis yang paling jarang ditemukan. Ketika perundungan hendak dikaitkan dengan tindak pidana maupun perdata, terdapat beberapa hal yang harus diteliti terkait dengan syarat masing-masing. Saat ini, peraturan perundang-undangan yang tersedia, seperti dalam KUHP, KUHPerdata, dan Undang-Undang Informasi dan Teknologi Elektronik, mampu mengikat pelaku perundungan secara umum. Peraturan yang bersifat khusus, seperti Undang-Undang Nomor 17 Tahun 2023 tentang Kesehatan, sudah mengatur perihal perundungan di lingkungan kedokteran, termasuk pendidikannya. Peraturan pelaksana yang lebih mengakomodir terkait penindakan perundungan dan penelitian mutakhir terkait kekuatan mekanisme hukum terkait perundungan masih sangat dibutuhkan.